A Treat-to-Target approach in hereditary angioedema: expert consensus from a European committee - Cancian, Mauro; Caballero, Teresa; Boccon-Gibod, Isabelle; Buttgereit, Thomas; Cohn, Danny; Eren, Efrem; Kiani-Alikhan, Sorena; Launay, David; Mandelin, Johanna; Zanichelli, Andrea; Farkas, Henriette (Frontiers in Immunology, 2026)
BackgroundHereditary angioedema (HAE) is a rare, unpredictable disease that imposes a substantial and multifaceted burden on patients’ daily lives, with many not achieving the World Allergy Organization (WAO)/European Academy of Allergy and Clinical Immunology (EAACI) recommended treatment goal of normalisation of life.MethodsIn March 2025, a European expert committee convened to discuss how to effectively implement WAO/EAACI guidelines in clinical practice, identifying a Treat-to-Target (T2T) approach to support consistent adoption of guideline recommendations into routine care. Through iterative expert discussion and consensus, a T2T algorithm was developed to support the achievement of optimal treatment goals for adolescents and adults with HAE, providing a structured, patient-centred strategy to guide HAE management. Feasibility and clarity of the consensus T2T algorithm were evaluated via an online survey of 64 European clinicians and 15 representatives from patient organisations. Feedback from the survey was used to refine the final version.ResultsThe T2T algorithm provides a visual, practical framework that offers guidance on initiating long-term prophylaxis (LTP), as well as setting and assessing individualised short- and long-term targets and treatment plans. Target attainment is achieved through regular monitoring, involving a comprehensive assessment of disease activity and burden, analysis of the causes of breakthrough attacks, and considering optimising management or switching LTP treatment when targets are not being reached. The ultimate goal of treatment for HAE is to achieve normalisation of life.ConclusionBy setting clear, measurable, and individualised treatment targets supported by shared decision-making, regular monitoring and treatment optimisation as needed, this consensus-derived T2T algorithm aims to promote more consistent care within the HAE community and ultimately improve patient outcomes.